2022
DOI: 10.1111/cns.13950
|View full text |Cite
|
Sign up to set email alerts
|

A novel severe cerebral venous thrombosis rat model based on semi‐ligation combined with ferric chloride and thrombin

Abstract: Aims An applicable cerebral venous sinus thrombosis (CVST) model is imperative for exploring its pathophysiology. We established a novel severe CVST model using semi‐ligation, ferric chloride, and thrombin. Methods A total of 138 male Sprague–Dawley rats were randomly divided into semi‐ligation (n = 75) and non‐semi‐ligation (n = 63) groups. A sham group (n = 46) was also included. We compared short‐term and long‐term neurological and cognitive dysfunction, mortality rates, thrombus load, venous infarction vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recently, we explored the pathological characteristics of CVT using a novel severe CVT rat model 42 and found that nonthrombotic internal jugular venous stenosis may be an interventional risk factor for CVT. 43 We discovered that BCAAs, as potential biomarkers, might play a role in distinguishing acute CVT, cerebral hemorrhage and cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we explored the pathological characteristics of CVT using a novel severe CVT rat model 42 and found that nonthrombotic internal jugular venous stenosis may be an interventional risk factor for CVT. 43 We discovered that BCAAs, as potential biomarkers, might play a role in distinguishing acute CVT, cerebral hemorrhage and cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The CVT rat model was performed as the previous method 12 . Under anesthesia, the rats were placed in a prone position, using iodophor as preoperative skin disinfectant, and an incision was made in the middle of each rat's head, and the subcutaneous tissue was separated to expose the skull.…”
Section: Methodsmentioning
confidence: 99%
“…The CVT rat model was performed as the previous method. 12 Under anesthesia, the rats were placed in a prone position, using iodophor as preoperative skin disinfectant, and an incision was made in the middle of each rat's head, and the subcutaneous tissue was separated to expose the skull. A longitudinal cranial window, which exposed the SSS and bilateral cortex, using a high‐speed dental drill through microscopic observation.…”
Section: Methodsmentioning
confidence: 99%
“…Ferroptosis is implicated in many neurological disorders such as traumatic brain injury (TBI) and in chronic neurodegenerative diseases including Alzheimer's disease and Parkinson's disease. 54 , 55 In the field of ischemic stroke, ferroptosis is more extensively studied in hemorrhagic stroke 56 , 57 , 58 , 59 as heme and iron are blood components. Indeed, ferroptosis was observed in neonatal rat hypoxic–ischemic brain injury models.…”
Section: Cell‐specific Role Of Nrf2 In the Acute Phasementioning
confidence: 99%